MEMERDEKAKAN LAPANGAN MERDEKA BARU DI KOTA MEDAN - Thierry Henry; Rudy Surya (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Merdeka Square in Medan City, the capital city of North Sumatra Province, with an area of 48,877 square meters has experienced a degradation pattern of space use or function conversion. Initially the Merdeka field was a Green Open Space (RTH) for the city of Medan as well as the lungs of the city and the heart of the city of Medan. In addition to the decline in the function of space, there is also a loss of image due to the development being carried out without regard to the main function and role of the field, which is an issue of significance that will be raised so that it can have a positive impact on the surrounding community of the area. So it is necessary to develop Merdeka Square by returning Green Open Spaces (RTH) which have passed local regulations, developing programs that can restore lost historical and cultural values in the area. Urban Acupuncture can be the answer to the problems that exist on Merdeka Square, with minimal changes but can have a big impact on Merdeka Square itself. The method used for the design is "form follow function", with this method the building is planned in a form that follows its function as a museum in which there are various activities including the museum itself, food court, retail and multifunction hall which can be used when there are events or events as well as performing arts by the public freely. The results of this design can be a future reference or description of the Merdeka Square area so that it can revive and develop for the better according to the function of green open space for the city of Medan. Keywords:  Conversion of functions; green open space; museum; the merdeka square; urban acupuncture Abstrak Lapangan Merdeka di Kota Medan, ibu Kota Provinsi Sumatera Utara, dengan luas 48.877 m² telah mengalami degradasi pola penggunaan ruang atau alih fungsi. Awalnya lapangan Merdeka ini merupakan Ruang Terbuka Hijau (RTH) Kota Medan sekaligus merupakan paru-paru Kota serta jantung dari Kota Medan. Selain telah terjadi penurunan fungsi ruang juga hilangnya citra akibat pembangunan yang dilakukan tanpa memperhatikan fungsi dan peran utama dari lapangan tersebut menjadi isu signifikansi yang akan diangkat agar dapat memberikan dampak positif untuk masyarakat sekitar. Sehingga perlu dilakukan pengembangan Lapangan Merdeka dengan mengembalikan Ruang Terbuka Hijau (RTH) yang di mana sudah melewati regulasi peraturan daerah setempat, mengembangkan program yang dapat mengembalikan nilai histori serta budaya yang hilang dikawasan tersebut. Urban Acupuncture dapat menjadi jawaban untuk permasalahan yang ada di lapangan Merdeka, dengan minimnya perubahan tetapi dapat berdampak besar bagi Lapangan Merdeka itu sendiri. Metode yang digunakan untuk perancangan adalah “form follow function”, dengan metode ini direncanakan bangunan dengan bentuk yang mengikuti fungsinya sebagai museum yang di dalamnya terdapat berbagai kegiatan diantaranya museum itu sendiri, foodcourt, retail serta multifunction hall yang dapat digunakan ketika ada event atau acara serta pergelaran seni oleh masyarakat secara bebas. Hasil dari perancangan ini dapat menjadi acuan atau gambaran kedepannya dari kawasan Lapangan Merdeka sehingga bisa hidup kembali dan berkembang menjadi lebih baik sesuai dengan fungsi RTH untuk Kota Medan.